Eating away cancer: the potential of diet and the microbiome for shaping immunotherapy outcome - Nguyen, Ngoc-Trang Adrienne; Jiang, Yan; McQuade, Jennifer L. (Frontiers in Immunology, 2024)
The gut microbiome (GMB) plays a substantial role in human health and disease. From affecting gut barrier integrity to promoting immune cell differentiation, the GMB is capable of shaping host immunity and thus oncogenesis and anti-cancer therapeutic response, particularly with immunotherapy. Dietary patterns and components are key determinants of GMB composition, supporting the investigation of the diet-microbiome-immunity axis as a potential avenue to enhance immunotherapy response in cancer patients. As such, this review will discuss the role of the GMB and diet on anti-cancer immunity. We demonstrate that diet affects anti-cancer immunity through both GMB-independent and GMB-mediated mechanisms, and that different diet patterns mold the GMB’s functional and taxonomic composition in distinctive ways. Dietary modulation therefore shows promise as an intervention for improving cancer outcome; however, further and more extensive research in human cancer populations is needed.